Financial Literacy as a Moderator in Behavioral Biases and Investor Decisions - Gupta, Nancy; Rana, Rachita; Tandon, Deepak (Indian Journal of Finance, 2025)
Purpose : The first objective of this research paper was to examine the impact of behavioral biases on investment decisions. Additionally, the second objective was to analyze the moderating role of financial literacy in the relationship between behavioral biases and investment decisions in a developing country like India. Design/Methodology/Approach : The conceptual framework was based on prospect theory and regret theory. The author considered six independent variables (herding bias, overconfidence bias, endowment bias, loss aversion bias, regret bias, and mental accounting bias), one dependent variable (investment decision), and one moderating variable (financial literacy). Data for the survey was collected using a structured questionnaire from 326 investors in Delhi and Noida. Findings : The findings of this study revealed that behavioral biases influenced investors’ decisions. Another key finding was that financial literacy moderated the relationship between biases and investment decisions. In summary, higher financial literacy made investors more capable of identifying and overcoming biases. This insight enabled investors to make more logical and well-informed investment decisions. Practical Implications : The research findings are significant for policymakers, managers, investors, and shareholders. Policymakers could design financial education programs and initiatives to improve financial literacy, fostering a more knowledgeable investor base. This will contribute to greater market stability. Originality/Value : Previous research frequently examined individual biases but did not explore the potential influence of financial literacy on these biases in conjunction with demographic factors in the Indian context.